033 Functional, molecular and genetic study of chronic granulomatous disease: the great ormond street experience. (December 2018) - Murphy, Claire; Plumbly, Patricia; Ralph, Elizabeth; Goldblatt, David; Gilmour, Kimberly
Abstract : Chronic Granulomatous Disease (CGD) is a primary immunodeficiency characterised by recurrent infection by intracellular pathogens due to a failure of neutrophils to undergo respiratory burst; many patients have inflammatory sequelae, including inflammatory bowel disease. Infection with catalase-positive organisms resulting in deep-seated abscesses, particularly of the liver, is a common initial presentation. CGD is genotypically heterogeneous with X-linked defects in CYBB (encoding gp91) as well as autosomal recessive defects in CYBA (p22phox), NCF1 (p47phox), NCF2 (p67phox) and NCF4 (p40phox) described. Great Ormond Street Hospital immunology laboratory uses the nitroblue tetrazolium and dihydorhodamine assays to assess neutrophil function. Lack of neutrophil respiratory burst triggers molecular CGD screening which covers all known genetic causes of CGD. The results of these molecular tests may be further verified by gene sequencing approaches. We present the data from 1168 patients investigated for CGD between January 2013 and January 2018. We identified: 13 patients with CYBB mutations from 9 families; 8 patients with NCF4 mutations from 2 families; 7 patients with NCF1 mutations from 5 families; a single patient with an NCF2 mutation and 3 patients with CYBA mutations from a single family. The review of this data revealed a unique characteristic of p40phox deficient patients; a normal NBT in the context of a reduced ability to undergo respiratory burst in response to Escherichia coli . This information will aid in the rapid diagnosis of subsequent patients with this condition. The development and implementation of the rapid molecular CGD testing, often as a proxy for genetic testing which takes significantly more time, has been essential in the early diagnosis and prompt treatment of these patients. Life expectancy for CGD patients has increased more than three-fold over the last few decades in part due to the development of rapid molecular CGD screening.